MENINGKATKAN MINAT BELAJAR ANAK MELALUI PENDEKATAN SAINTIFIK PADA ANAK USIA 5-6 TAHUN DI TK RIDHA KECAMATAN SUKAJADI KOTA PEKANBARU - Putri, Anita; ', Zulkifli N; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to determine how high the increased interest in studying children aged 5-6 years in kindergarten RIDHA Sukajadi city districts pekanbaru using approach. This research is a classroom action research conducted in 2. Data collection tool used in this study is in the form of sheets. The number of samples in this study were 15 children consisting of 9 boys and 6 children girls. Based on the analysis of the assessment process there was an increase of 2 cycles. The result of this research are very satisfying because getting the average value is very significant from before action to cycle I and cycle I to cycle II, that is from the average value 39,58 increased to 50,35 by percentage 27%, and from 50,35 increased 76,53 by percentage 52%. From the results of these studies concluded that the scientific approach to learning by giving a positive response to children and able to increase interest in learning in children.Key Words: Interest in learning, scientific approach